H2AFZ Is a Prognostic Biomarker Correlated to TP53 Mutation and Immune Infiltration in Hepatocellular Carcinoma - Dong, Mingwei; Chen, Jing; Deng, Yiran; Zhang, Danying; Dong, Ling; Sun, Dalong (Frontiers in Oncology, 2021)
H2A family member Z (H2AFZ) is a highly conserved gene encoding H2A.Z.1, an isoform of histone variant H2A.Z, and is implicated in cancer. In this study, we report that overexpression of H2AFZ is associated with tumor malignancy and poor prognosis in HCC patients. Functional network analysis suggested that H2AFZ mainly regulates cell cycle signaling and DNA replication via pathways involving several cancer-related kinases and transcription factor E2F1. Further studies revealed that H2AFZ overexpression is regulated by TP53 mutation and led to an attenuation of rapid proliferation phenotype and aggressive behavior in HCC cells. Moreover, we found that H2AFZ was related to immune infiltrations and was co-expressed with immune checkpoint genes, including CD274 (PD-L1), CTLA-4, HAVCR2 (TIM3), LAG3, PDCD1 (PD-1), and TIGIT (VSIG9) in HCC, indicating that H2AFZ-overexpressed HCC patients may be sensitive to immune checkpoint blockades (ICBs). Integrated analysis suggested that H2AFZhigh/TP53mut patients had the shortest OS and PFS time, but most likely to respond to ICBs. These findings indicate that the H2AFZ possesses potential value as a novel prognostic indicator for HCC patients and is correlated with immune infiltration in HCC, laying a foundation for future study of HCC investigation and intervention.